2019
DOI: 10.2196/13415
|View full text |Cite
|
Sign up to set email alerts
|

Web-Based Interventions to Improve Mental Health in Home Caregivers of People With Dementia: Meta-Analysis

Abstract: Background Dementia is a major cause of disability and dependency in older adults worldwide. It is often accompanied by general psychological distress, such as depression and anxiety symptoms, among caregivers of people with dementia (PwD). The physical and mental health of the caregiver is a prerequisite and a promise to help PwD continue to live as long and as well as possible. Web-based interventions can provide convenient and efficient support and an education tool to potentially reduce the ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
66
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(73 citation statements)
references
References 38 publications
7
66
0
Order By: Relevance
“…Despite the increase in research in this area -it has been estimated that the number of publications in this eld increases by 13% each year, including several systematic reviews -we could nd very little published with respect to the implementation of web-based caregiver interventions. (9)(10)(11)(23)(24)(25)(26) Moreover, many of the interventions described in the literature do not appear to be more broadly accessible outside of their research context. To our knowledge, no previous research has used the CFIR framework to study webbased caregiver interventions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the increase in research in this area -it has been estimated that the number of publications in this eld increases by 13% each year, including several systematic reviews -we could nd very little published with respect to the implementation of web-based caregiver interventions. (9)(10)(11)(23)(24)(25)(26) Moreover, many of the interventions described in the literature do not appear to be more broadly accessible outside of their research context. To our knowledge, no previous research has used the CFIR framework to study webbased caregiver interventions.…”
Section: Discussionmentioning
confidence: 99%
“…7Various systematic reviews suggest that web-based interventions may result in a range of improved health outcomes for caregivers, including reductions in depression, stress, distress and anxiety. (8)(9)(10)(11) Other studies have identi ed that greater public education is needed for caregivers, and improved mechanisms are needed for busy clinicians to provide caregiver education. (12) We developed iGeriCare (www.igericare.ca), a multimodal e-learning intervention to help educate family caregivers of people with dementia.…”
Section: Introductionmentioning
confidence: 99%
“…In Zhao et al (2019) Internet-based interventions on the mental health outcomes of family dementia caregivers was examined and the components of the Web-based interventions that play significant roles were explored [36]. Among the 815 caregivers who participated in six studies, four of the studies explored depression as an outcome where results showed that scores were reduced by an average of 0.23 (95% CI -0.38 to -0.07 ; p<.01) after Web-based interventions [36]. The average scores of two caregivers who were experiencing anxiety symptoms dropped by 0.32 points (95% CI -0.50 to -0.14; p<.01) [36].…”
Section: Analysis Synthesis and Outcomesmentioning
confidence: 99%
“…Among the 815 caregivers who participated in six studies, four of the studies explored depression as an outcome where results showed that scores were reduced by an average of 0.23 (95% CI -0.38 to -0.07 ; p<.01) after Web-based interventions [36]. The average scores of two caregivers who were experiencing anxiety symptoms dropped by 0.32 points (95% CI -0.50 to -0.14; p<.01) [36]. While this study shows that Web-based interventions were effective for anxiety in dementia caregivers, results were relatively poor when applied to coping, pain, and stress.…”
Section: Analysis Synthesis and Outcomesmentioning
confidence: 99%
See 1 more Smart Citation